2013
DOI: 10.1021/ma4017532
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoresponsive Healable Metallosupramolecular Polymers

Abstract: The development of polymers that possess superb mechanical properties and at the same time are capable of sensing damage and self-healing is presented. Coppercatalyzed azide−alkyne cycloaddition (CuAAC) based tridentate ligand 2,6-bis(1,2,3-triazol-4-yl)pyridine (BTP) and covalent mechanophore spiropyran (SP) units are incorporated into the polymer backbone to prepare ligand macromolecule. Upon coordinating with transition or lanthanide metal salts, metallosupramolecular films with phased-separated soft/hard m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 69 publications
4
101
0
Order By: Relevance
“…117 Both of these systems involved polymeric poly-btp components. More recently, Weng and co-workers have also reported self-healing btp systems with stress-sensing abilities, 163 and PEG-linked systems, which formed multiresponsive gels both in the presence and absence of Eu(III). 164 We reported [Ru(4b) 2 ](PF 6 )Cl, the first example of a metal complex gelator derived from discrete mono-btp components, the X-ray crystal structure of which suggests that it is able to induce solvent gelation by the formation of supramolecular polymer chains through hydrogen bond interactions between the carboxylic groups, ethanol solvent molecules and chloride anions.…”
Section: Metallo-supramolecular Gelsmentioning
confidence: 99%
“…117 Both of these systems involved polymeric poly-btp components. More recently, Weng and co-workers have also reported self-healing btp systems with stress-sensing abilities, 163 and PEG-linked systems, which formed multiresponsive gels both in the presence and absence of Eu(III). 164 We reported [Ru(4b) 2 ](PF 6 )Cl, the first example of a metal complex gelator derived from discrete mono-btp components, the X-ray crystal structure of which suggests that it is able to induce solvent gelation by the formation of supramolecular polymer chains through hydrogen bond interactions between the carboxylic groups, ethanol solvent molecules and chloride anions.…”
Section: Metallo-supramolecular Gelsmentioning
confidence: 99%
“…Gels swollen in acetonitrile or THF and crosslinked with Zn(OTf) 2 or Eu(OTf) 3 demonstrated excellent self-healing behavior. Another approach using CuAAC to copolymerize BIP and spiropyran (SP) in a polyurethane backbone was shown [197]. The addition of Zn 2+ or Eu 3+ leads to the formation of supramolecular gels revealing a hard/soft morphology.…”
Section: Self-healing Metallopolymersmentioning
confidence: 99%
“…Furthermore, if a sample was stretched, activating the spiropyrans, then irradiated with light whilst being held at constant strain to close the merocyanines, it was found that the spiropyrans opened once more after 1-2 h, demonstrating force-induced change in the energy landscape of the spiropyran-merocyanine transformation. Lastly, spiropyran has also been employed in combination with supramolecular cross-links, such as hydrogen-bonding dimers [15] and transition metal or lanthanide complexes [25], to create stress-reporting, self-healing gels.…”
Section: Spiropyran Mechanochromismmentioning
confidence: 99%